Integrative transcriptomic and protein analysis of human bronchial BEAS-2B exposed to seasonal urban particulate matter. (February 2016) - Longhin, Eleonora; Capasso, Laura; Battaglia, Cristina; Proverbio, Maria Carla; Cosentino, Cristina; Cifola, Ingrid; Mangano, Eleonora; Camatini, Marina; Gualtieri, Maurizio
Abstract: Background: Exposure to particulate matter (PM) is associated with various health effects. Physico-chemical properties influence the toxicological impact of PM, nonetheless the mechanisms underlying PM-induced effects are not completely understood. Objectives: Human bronchial epithelial cells were used to analyse the pathways activated after exposure to summer and winter urban PM and to identify possible markers of exposure. Methods: BEAS-2B cells were exposed for 24 h to 10 μg/cm 2 of winter PM2.5 (wPM) and summer PM10 (sPM) sampled in Milan. A microarray technology was used to profile the cells gene expression. Genes and microRNAs were analyzed by bioinformatics technique to identify pathways involved in cellular responses. Selected genes and pathways were validated at protein level (western blot, membrane protein arrays and ELISA). Results: The molecular networks activated by the two PM evidenced a correlation among oxidative stress, inflammation and DNA damage responses. sPM induced the release of pro-inflammatory mediators, although miR-146a and genes related to inflammation resulted up-regulated by both PM. Moreover both PM affected a set of genes, proteins and miRNAs related to antioxidant responses, cancer development, extracellular matrix remodeling and cytoskeleton organization, while miR-29c, implicated in epigenetic modification, resulted up-regulated only by wPM. sPM effects may be related to biological and inorganic components, while wPM apparently related to the high content of organic compounds. Conclusions: These results may be helpful for the individuation of biomarkers for PM exposure, linked to the specific PM physico-chemical properties. Graphical abstract: Highlights: PM induces activation of pro-inflammatory, oxidative stress and DNA damage pathways. Cancer, extracellular matrix and cytoskeleton remodelling pathways are modulated. PM induces the modulation of microRNAs. Possible biomarkers for PM exposure are proposed. Abstract : Exposure to particulate matters determines the activation of significant biological pathways and possible markers of exposure were identified.